CONCEPTUALIZATION OF ISLAMIC POLITICAL COMMUNICATION: ANALYSIS OF SCOPE, OBJECTIVES, FUNCTIONS, AND ETHICS BASED ON QUR'ANIC VALUES - Annisa Ariftha; Anang Anas Azhar (Program Pascasarjana UIN Sumatera Utara, 2026)
This article aims to examine the concept of political communication from an Islamic perspective, emphasizing the scope, objectives, functions, theories, and ethics of political communication derived from the values of the Qur'an. This study is motivated by the importance of political communication as a strategic instrument in building relationships between political actors, institutions of power, the media, and society. From an Islamic perspective, political communication is not only understood as a process of conveying messages related to power and public interests, but also as a social practice that must be based on the principles of honesty, justice, trustworthiness, propriety, and the welfare of the people. This article uses a qualitative approach based on literature review by examining various relevant literature on political communication, Islamic communication, political communication theory, and the ethical principles of communication in the Qur'an. The results of the study indicate that Islamic political communication has a scope that includes political communicators, political messages, political media, audiences, and communication effects. The objectives of Islamic political communication are directed at building political awareness, socializing values, articulating interests, and creating a political order oriented towards the welfare of the people. Furthermore, the functions of Islamic political communication include conveying information, political education, advocacy, publication, social control, and shaping public opinion. The ethics of political communication in the Qur'an emphasize the principles of qaulan sadidan (consistency), tabayyun (intelligence), justice, and moral responsibility. Thus, Islamic political communication can serve as a normative framework for establishing civilized, transparent, participatory political practices that are oriented toward moral and spiritual values.